Cultural Challenges to Weight Management: A Qualitative Study of Saudi Women's Experiences. Issue 1 (2nd January 2022) - Alissa, Nawal A.
ABSTRACT: Purpose: To explore and describe the experiences of Saudi women with obesity regarding cultural barriers that prevent them from following dietary and physical activity recommendations. Design: Phenomenological qualitative study. Methods: A focus group (4 participants) and individual interviews (13 participants) were conducted from seventeen women participating in a nutrition and weight management program. Findings: Several themes were identified based on experiences and consequences of cultural restraints. Conclusions: Findings provide an understanding of how cultural factors impede Saudi women with obesity from achieving effective weight management. Clinical Evidence: Designing weight management programs that are individualized and consider the differences in how women are culturally affected provide more effective interventions for women with obesity.